Influence of functional foot orthoses on the plantar pressure of 5 handball athletes: analysis using a novel system during 3 athletic tasks - Esteves, J.; Luz, A.; Fidalgo, R.; Briôa, M.; Matos, J. P. (6th ENBENG - IEEE Portuguese Meeting in Bioengineering, ISEL, Lisbon (Portugal), February 22-23, 2019, 2019)
In sports involving high impact forces, like handball, the intense effort alongside the set of repetitive motions is connected with an increase on forefoot plantar pressure consequently increasing injury probability. As a preventive measure, the use of functional foot orthoses (FFO) is recommended for plantar pressure redistribution. The goal of this study was to determine functional foot orthoses influence on forefoot plantar pressure, during three athletic movements. Two tests were performed in five athletes, one with the standard insole and the other with a functional foot. Results indicated that the functional foot orthoses reduced plantar pressure. Meanwhile, only for hallux and the middle forefoot regions were found statistically significant reductions, when performing side cut task. Further investigation is needed in order to verify the significance of functional foot orthoses use in sports. Sample size increase of our study is a potential improvement in the future as well as reproducibility of course tests to meliorate the understanding of specificrelated sports tasks.